2009
DOI: 10.1128/aem.02343-08
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Pig Fecal Contamination in a River Catchment by Real-Time PCR Using Two Pig-Specific Bacteroidales 16S rRNA Genetic Markers

Abstract: The microbiological quality of coastal or river water can be affected by fecal contamination from human or animal sources. To discriminate pig fecal pollution from other pollution, a library-independent microbial source tracking method targeting Bacteroidales host-specific 16S rRNA gene markers by real-time PCR was designed. Two pig-specific Bacteroidales markers (Pig-1-Bac and Pig-2-Bac) were designed using 16S rRNA gene Bacteroidales clone libraries from pig feces and slurry. For these two pig markers, 98 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
173
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(191 citation statements)
references
References 43 publications
17
173
1
Order By: Relevance
“…Since its development, 2966 individual non-human fecal samples have been screened for the presence of the HF183 marker, of which 2807 were PCR negative, yielding an overall host specificity value of 94.6% (Supplementary Table S11). Several studies have reported 100% host specificity of the HF183 marker for non-human fecal samples [51,[66][67][68][69][70]. In contrast, the occasional presence of the HF183 markers in non-human fecal samples has also been reported [52,57,61,71,72], particularly in dog, deer, and chicken feces.…”
Section: Host Specificitymentioning
confidence: 91%
“…Since its development, 2966 individual non-human fecal samples have been screened for the presence of the HF183 marker, of which 2807 were PCR negative, yielding an overall host specificity value of 94.6% (Supplementary Table S11). Several studies have reported 100% host specificity of the HF183 marker for non-human fecal samples [51,[66][67][68][69][70]. In contrast, the occasional presence of the HF183 markers in non-human fecal samples has also been reported [52,57,61,71,72], particularly in dog, deer, and chicken feces.…”
Section: Host Specificitymentioning
confidence: 91%
“…Significant concentrations of dissolved DNA are found in marine water, freshwater, and sediments, potentially complicating the interpretation of information from qPCR data due to the relatively long persistence of target DNA (23). The PMA-qPCR method could avoid the issue of persistent DNA and provide a relatively fast, simple, and inexpensive means to discriminate intact/dead cells in mixed populations (2,22,42). However, some limitations of PMA-qPCR have been reported, such as the interference of higher particle concentration (2) and highly complex chemical and biological matrices in environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FIB are inadequate to identify the source of fecal pollution because they are observed in both warm-and cold-blooded animal feces (30,35). Microbial source tracking (MST) can discriminate between human and nonhuman fecal contamination such as cow, dog, and pig in water using microbiological or chemical traits of source identifiers (19,22). Bacteroidales have been proposed as an alternative fecal indicator as well as source identifier because they are abundant in the gastrointestinal tract and genetic markers based on 16S rRNA have host-associated distributions (7,13,14,17,18,25,30,32).…”
mentioning
confidence: 99%
“…The Bacteroidales counts were high compared to the number of E. coli that are occasionally observed in fecally contaminated drinking water (17a) but low compared to numbers observed in surface water (4,20,22). Water from the extraction wells and raw water used for unchlorinated drinking water production were analyzed, and Bacteroidales species were detected in 10 out of 15 samples (Table 1).…”
mentioning
confidence: 99%